2005 International Conference on Simulation of Semiconductor Processes and Devices 2005
DOI: 10.1109/sispad.2005.201534
|View full text |Cite
|
Sign up to set email alerts
|

Joule Heating under Quasi-Ballistic Transport Conditions in Bulk and Strained Silicon Devices

Abstract: We use Monte Carlo simulations to examine self-heating in ultra-short silicon devices when quasiballistic transport conditions dominate. The generated phonon spectrum in strained silicon is found to be different from bulk silicon at low electric fields, but essentially the same under high fields. Joule heat dissipation in ultra-short devices occurs almost entirely in their drain region, since transport across the channel is quasiballistic. The results of this work can be used to gauge the electro-thermal perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 13 publications
4
31
0
Order By: Relevance
“…The influence of the boundaries is not directly seen in equation (1.1) but can be reflected by the imposed boundary conditions. Various methods have been used to investigate the in-plane thermal transport in nanofilms with internal heating [4][5][6][7][8]. Through solving the phonon Boltzmann transport equation, Sverdrup et al [4] found that the peak temperature rise in the nanofilms could be significantly larger than the prediction using the heat diffusion equation based on Fourier's law.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the boundaries is not directly seen in equation (1.1) but can be reflected by the imposed boundary conditions. Various methods have been used to investigate the in-plane thermal transport in nanofilms with internal heating [4][5][6][7][8]. Through solving the phonon Boltzmann transport equation, Sverdrup et al [4] found that the peak temperature rise in the nanofilms could be significantly larger than the prediction using the heat diffusion equation based on Fourier's law.…”
Section: Introductionmentioning
confidence: 99%
“…Narumanchi et al [5] discussed the influence of the range and duration of heat generation on the temperature distribution evolutions within the nanofilms. Pop et al [6] analysed the heat generation and transport in nanoscale transistors using the Monte Carlo (MC) simulations. Wong et al [7] studied the effect of ballistic phonon transport in the nanofilms with heat generation via the MC simulations.…”
Section: Introductionmentioning
confidence: 99%
“…At sufficiently high power densities (~10 12 W/cm 3 ) and length (temporal) scales well below the relaxation length (time), i.e. < 100 nm (< 10 ps), of the energy carriers, both hot electron and hot phonon effects are to be anticipated [6,7]. Such conditions could be encountered in highly scaled transistors.…”
Section: Introductionmentioning
confidence: 99%
“…The heat generation rate is computed as a sum of all phonon emission events minus all phonon absorption events. Hence, complete phonon generation spectra can be obtained both for bulk silicon samples (e.g., as a function of electric field) and in various device geometries [5]. In particular we find that the heat generation region extends far into the drain of nanoscale devices (Fig.…”
Section: Joule Heating In Bulk and Strained Silicon Devicesmentioning
confidence: 75%
“…The generation rates for the other phonon modes are either smaller or their density of states (DOS) is larger (the DOS is proportional to the square of the phonon wave vector, which is largest at the edge of the Brillouin zone) and nonequilibrium effects are less significant. Assuming a 10 ps phonon lifetime [8] we find the occupation number of the g-type LO phonon to exceed N LO > 0.1 and become comparable to unity for power densities greater than 10 12 W/cm 3 [5]. Such power densities are attainable in the drain of 20 nm (or shorter) channel length devices at operating voltages from the current ITRS guidelines (Fig.…”
Section: Joule Heating In Bulk and Strained Silicon Devicesmentioning
confidence: 80%